2020
DOI: 10.1155/2020/3896386
|View full text |Cite
|
Sign up to set email alerts
|

Laser Treatment for Melanin Gingival Pigmentations: A Comparison Study for 3 Laser Wavelengths 2780, 940, and 445 nm

Abstract: The normal appearance of the gingiva is pink to light red, and this appearance may change due to many factors and might be noticeable causing aesthetic concerns. In the Gulf area, the gingival melanin pigmentation is of the main type of concern, and patients expect the pigmentation to be removed for aesthetic reasons. Many techniques have been used to remove the melanin pigmentation such as using surgical blades, diamond or ceramic burs, chemicals, and lasers. This study is comparing the results of three laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…6 Several chromophores, such as melanin and hemoglobin, are present in periodontal tissue. 15,16 In this study, the diode laser employed to image periodontal tissue has a wavelength of 532 nm. Several chromophores in biological tissues absorb light effectively at these wavelengths, including melanin and hemoglobin, which have absorption coefficients of 750 cm -1 and 230 cm -1 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…6 Several chromophores, such as melanin and hemoglobin, are present in periodontal tissue. 15,16 In this study, the diode laser employed to image periodontal tissue has a wavelength of 532 nm. Several chromophores in biological tissues absorb light effectively at these wavelengths, including melanin and hemoglobin, which have absorption coefficients of 750 cm -1 and 230 cm -1 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Er, laser gave the shortest time before the recurrence of gingival pigmentation. Taher Agha & Polenik (2020) reported that both diode and Erbium lasers were fast, proficient in removing the pigmentations and well accepted by the patients [18]. The aesthetic outcomes were certainly encouraging, and the patients were extremely satisfied.…”
Section: Resultsmentioning
confidence: 97%
“…A clinical study that compared different wavelengths has found that melanin pigments effectively absorb the diode laser energy, enhance faster peeling, and cause no relapse as compared to an erbium laser. [31]. Although no specific mode for depigmentation is available in the system, it showed that this procedure could be performed safely with the dual-wavelength diode laser.…”
Section: Discussionmentioning
confidence: 96%